(untitled) (TAJ: Journal of Teachers Association, 2019)
Stroke ranks first in frequency among all the neurological diseases of adult life and about 50% of all neurological disorders in a hospital are of this type. It is the third leading cause of death throughout the world. The purpose of the present study was to find out the presence or absence of haemorrhage or infarct and to detect the early signs of stroke on the basis of CT scanning. Three-hundred twenty one consecutive acute stroke patients (mean age 64 ±9.75 years) were included in our study. Each underwent cranial computed tomography without intravenous contrast injection within the first 24 hours. CT findings of stroke were analyzed using SPSS software. Among 321 patients, 209(65.11%) had ischemic stroke, 99(30.84%) had parenchymal haemorrhage and 13(4.05%) had subarachnoid haemorrhage. Total amount of haemorrhagic stroke was 112(34.89%). Early CT findings of ischaemic stroke were low attenuation area (83.25%), sulcal effacement (69.89%), loss of the insular ribbon (17.70%), hyperdense artery sign (1.43%). CT scanning should be the first line of investigation for diagnosis of acute stroke as it is more available than MRI and is easily performed in severely ill patients who are dependent on support and monitoring devices TAJ 2019; 32(1): 17-24